Effect of cryorolling and room temperature rolling on 6082 Al alloy - Kumar V.; Kumar D.; Singh I.V.; Mishra B.K. (My University, 2025)
The 6082Al alloy has been worked on at both cryogenic and ambient temperatures in this chapter. Tensile testing has been used to determine how cryorolling and room temperature rolling have affected materials. Tensile characteristics also demonstrate the effectiveness of the heat treatment regimen. Due to grain refinement, grain fragmentation, high angle boundaries, and the creation of ultrafine grains, the microstructure of the cryorolled (CR) and room temperature rolled (RTR) 6082 Al alloy with varied thickness reductions, i.e. 40%, 70%, and 90%, is characterised by electron back scattered diffraction (EBSD) and transmission electron microscopy (TEM). As a result of improved tensile strength, CR exhibits better mechanical qualities than RTR alloy. © 2024 selection and editorial matter, Saumya Shah, Hemant Nautiyal, Gaurav Gugliani, Ashwani Kumar, Tanuj Namboodri and Yogesh Kumar Singla; individual chapters, the contributors.